(3Gdbhd GdebJUH aj eG hGab dZI Cgd eUQ ef dZGJ GdYQHs - (3eMeO Hf eMeO CHi GdSQhQ Hf eMeO GdHcQi GdUOjb GdeYQha HGHf CHi GdSQhQs; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CWdY HOhQ GdLeGdGJ GdjhSajI aYeJ GdOjGQ GdeUQjI hHYO , aEfi WGdYJ cJGH QaY GdEUQ Yf cdGe Cgd eUQ aNWQ di Cf CdNU eeG Sfg s
(3BNQgG (B:s
(3aUd GdgGA (B: (3jbhdhf (B: (3adGf gajI hCeG GdhGh hGdjGA ef MQa GdjGA aEfg de jQO , aEf de jQO ajgeG TF gPG BNQ eG CQOfGg hJeG e eG bUOfGg s
(3GfJgi ef JCdjag ai TgQ QHjY GdKGfi SfI (B1057(3g`s
(3HgG eTgG djhSa Gdedhi GdTgjQ H GHf Gdhcjd JYdjbGJ egeI HNWs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs